An attempt for measuring snowboarding performance using compact force sensors - Kondo, A.; Doki, H.; Hirose, K. (Procedia Engineering, 2014)
This paper deals with the development of measurement system of reaction force from snow surface for snowboarding by compact size force sensors. This system consists of four 3-lightweight and compact axis force sensor. A comparison between the system and a 6-axis force sensor confirmed the precision of the system. The results of proposed system and 6-axis force sensor were approximately fitted in all axes. Further, the system was used to measure carving turns performed on snow field. The results indicated the reaction force from snow surface of 6-axis components in gliding on the actual snow field. The reaction force from snow surface in gliding on the actual snow field can be measured by using this system, and this system is more compact and lighter than the previous system. Hence, this system can be reduced restraint of snowboarder by the measurement system. Then, this system can be used to resolve the mechanism of snowboard turns and to evaluate the skill of snowboarder.